A pricing model for callable bonds - Castillo R., Augusto; Valenzuela D., Alejandro (Estudios de Administración, 2005)
This paper describes different types of callable bonds. It also presents a model to value those callable bonds when interest rates follow a stochastic process, inspired in the model to value American options developed by Longstaff and Schwartz (2001), known as the Least Squares Montecarlo algorithm. The proposed methodology is applied to the valuation of two semi American callable bonds. A sensibility analysis is developed for the bond´s values and for the option´s values included in the bonds.